UTILIZING INSTAGRAM TO DEVELOP STUDENTS WRITING SKILLS - Sari, Monika (JOEEL (Journal of English Education and Literature), 2023)
English is important to learn, English language has four skills that have to learn by students. There are Listening, Speaking, Reading, and Writing. In this research, the writer wants to make some research about how to increase the writing skill of the students in class X Fashion Design SMK Negeri 8 Surabaya. By using Instagram as a media to teach the student with the method of Classroom Action Research (CAR) for this research. The subject of the research is 36 students of Class X Fashion Design 2. Based on the research the writer finds, that in cycle 1, the writing skill of the students was just 36,10 %. Of 36 students only 13 students can be passed the minimum score. After using the Instagram media method or on cycle 2 the writer finds 88% or 32 students from 36 students can be passed the score minimum. It means if the writer succeeds in using the method to improve the students writing skills, especially on Descriptive Text.